Effect of some indigenous medicinal plant extracts on Fasciola gigantica in vitro - KUSHWAHA, D S; KUMAR, D; TRIPATHI, H C; TANDAN, S K (The Indian Journal of Animal Sciences, 2014)
Extracts from indigenous medicinal plants, viz. Carica papnya (papeeta), Mallotus philippinensis (kamala) and Azadirachta indica (neem) were screened against Fasciola gigantica in vitro to develop safer, cheaper and effective remedy for fascioliasis in ruminants. Effects of plant extracts were evaluated on the gross visual motility, glucose uptake, glycogen and lactic acid contents and AChE activity of liverfluke. Cumulative concentrations of the plant extracts were applied on isimetricallu mounted fluckes, M. philippinensis (300 and 1000 µg/ml concentration) inhibited the frequency and and amplitude of the liverfluke and paralysed it finally. M. philippinensis (30 µg/ml) and A. indica (30 µg/ml) and C,. papaya (10 µg/ml) depleted the glycogen contents significantly. M phulippinensis and A. indica (30 µg/ml) increased the lactic acid contents of the fluke. Gross visual motility of the fluke became nil following 4 hr incubation in M. philippillensis and A. indica (30 µg/ml). It is concluded that M. philippinensis and A. indica extracts possess inhibitory effects on the spontaneous muscular activity of F. gigantica in vitro.